Basic mechanisms of platelet receptor shedding. (19th May 2017) - Andrews, Robert K.; Gardiner, Elizabeth E.
Abstract: Proteolytic shedding of the extracellular ectodomain of platelet receptors provides a key mechanism for irreversible loss of ligand-binding capacity, and for regulating platelet function in health and disease. Platelets derived from megakaryocytes are small anucleate cells in peripheral blood, with the ability to rapidly adhere, become activated, and secrete an array of procoagulant and proinflammatory factors at sites of vascular injury or disease, and to form a platelet aggregate (thrombus) which is not only critical in normal hemostasis and wound healing, but in atherothrombotic diseases including myocardial infarction and ischemic stroke. Basic mechanisms of receptor shedding on platelets have important distinctions from how receptors on other cell types might be shed, in that shedding is rapidly initiated (within seconds to minutes) and occurs under altered shear conditions encountered in flowing blood or experimentally ex vivo . This review will consider the key components of platelet receptor shedding, that is, the receptor with relevant cleavage site, the (metallo)proteinase or sheddase and how its activity is regulated, and the range of known regulatory factors that control platelet receptor shedding including receptor-associated molecules such as calmodulin, factors controlling sheddase surface expression and activity, and other elements such as shear stress, plasma membrane properties, cellular activation status or age. Understanding these basic mechanisms of platelet receptor shedding is significant in terms of utilizing receptor surface expression or soluble proteolytic fragments as platelet-specific biomarkers and/or ultimately therapeutic targeting of these mechanisms to control platelet reactivity and function.